Effect of Alkaline 5% NaOH treatment with variations of immersion time on tensile strength and flexural strength of Betung bamboo internode - Zulhanif Zulhanif; Firlli Abim Mahtata; Mohammad Badaruddin (Journal of Integrated and Advanced Engineering (JIAE), 2022)
Betung bamboo has a bigger stem diameter, thicker walls, and shorter internodes than other species of bamboo, making it ideal for building materials such as bridges and interior furnishings that may also be turned into works of art. Alkaline NaOH treatment was introduced to Betung bamboo to increase its mechanical properties. The alkaline treatment used a solution consisting of 5 %NaOH. Specimens with alkaline treatment were immersed into 5%NaOH solution for one hour, two hours, and three hours, followed by two hours of drying in a furnace at 60 °C. Tensile tests (ASTM D638) and flexural tests (ASTM D790) were carried out using servo hydraulics MTS Landmark 100 kN under static loading. The tensile strength, modulus of rupture (MOR) and modulus of elasticity (MOE) were analyzed from the results tests. The average maximum tensile strength of the Betung bamboo internode immersed for two hours into 5%NaOH solution is about 195.95 MPa, whereas the average values of MOR and MOE are about 207.35 MPa and 4.56 GPa, respectively. The faults and surface conditions in the Betung bamboo internode were observed using fractographic and morphological observations.